Deep chlorophyll maximum in temperate lakes with different trophic conditions − a rare or common phenomenon? - Karpowicz Maciej; Pasztaleniec Agnieszka; Grabowska Magdalena; Pietryczuk Anna (Knowledge and Management of Aquatic Ecosystems, 2024)
Deep chlorophyll maxima (DCM) are a common phenomenon in low-trophic stratified lakes, and there is much less information about the occurrence of DCM in eutrophic and dystrophic lakes. Therefore, we performed in situ continuous measurements of chlorophyll concentration by a submersible spectrofluorometer in 23 temperate lakes with different trophic conditions (mesotrophic, eutrophic, and dystrophic). We perform chemical analyses of available nutrient forms to better understand the mechanism of DCM formation. We found the highest concentration of phytoplankton in the metalimnion or upper hypolimnion of most studied lakes, regardless of trophic conditions. Nevertheless, the differences in the number of phytoplankton between DCM and epilimnion were largest in low-trophic lakes, where the chl a concentration in DCM was even 15 times higher than that in the epilimnion. The mesotrophic lakes showed vertical niche segregation by phytoplankton, with a general pattern − green algae in the upper layer, below diatoms, then cryptophytes (and cyanobacteria). Our results indicated that the main factor for DCM in mesotrophic and eutrophic lakes was epilimnetic nutrient depletion, while in dystrophic lakes, it seems to be caused by other factors due to the depletion of dissolved nutrients in whole water profiles.